The impact of electronic distribution channels on the tour operators market in Poland - Gołembski, Grzegorz; Andrzejewski, Maciej (Economics and Business Review, 2006)
On the basis of secondary analysis of data from the Polish market of e-commerce, we have made an attempt to verify a working hypothesis concerning achieving competitive advantage by tour operators who actively apply the electronic distribution channels. After having described the structure of the Polish tour operator market, we carried out research of tourism services sale on the market of e-commerce. We marked out the distribution channels B2B that streamline cooperation between tour operators and agents, as well as between providers and agents -that is an effect of diminishing barriers of entering for new companies. We also distinguished the distribution channels B2C providers (being a result of an increase of their bargaining power) as well as tour operators (through their own reservation website, e-shops or other forms of advanced technology application). Moreover, we emphasised the role of e-commerce in achieving competitive advantage by diversification of an offer or through a better market segmentation. (original abstract)